IMPLEMENTASI PEMBELAJARAN ANSAMBEL PIANIKA DALAM MENGEMBANGKAN KETERAMPILAN TEKNIK DASAR DAN KEKOMPAKAN BERMAIN WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS III RANGKASBITUNG - Sirojul Huda, Fuad; Dadang Dwi Septiyan; Alies Triena Permanasari; Adi Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Music education is one of the personality development programs that can be implemented in correctional institutions as a means of enhancing skills, character building, and social competence among inmates. This study aims to describe the implementation of pianica ensemble learning in developing basic technical skills and ensemble cohesion among inmates in correctional institutions. The research employed a qualitative approach with a descriptive method. The participants consisted of five inmates who took part in a pianica ensemble program conducted over twelve meetings. Data were collected through observations, in-depth interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of pianica ensemble learning was carried out through stages of planning, instruction, and evaluation. The learning process was conducted gradually, beginning with the introduction of the instrument, basic playing techniques, simple music notation, and group ensemble practice. The program successfully improved participants’ basic technical skills, including proper instrument handling, fingering techniques, breath control, and pitch accuracy. In addition, ensemble activities enhanced group cohesion through the ability to follow tempo, maintain rhythm, communicate effectively, and collaborate with fellow players. Supporting factors included participants’ motivation, support from correctional officers, and the application of structured and continuous practice. Meanwhile, limited facilities and varying initial skill levels posed challenges during the learning process. Therefore, pianica ensemble learning contributes positively to the development of both musical and social skills among inmates in correctional institutions.